Concentrations of organotin compounds in aquatic biota in coastal waters of Johor, Malaysia - Ohji, Madoka; Shibayama, Kota; Harino, Hiroya; Hayashizaki, Ken-Ichi; Md. Yusoff, Fatimah; Inoue, Koji (Cambridge University Press, 2022)
The concentrations of organotin (OT) compounds, butyltin (BT) and phenyltin (PT), in aquatic organisms from Merambong and Tinggi Island, Malaysia, which differ in industrial and economic activities, were measured. Tributyltin (TBT) compounds among BTs ranged from 2.9–28 and <0.1–21 ng g−1 ww in aquatic organisms from Merambong and Tinggi Island, respectively. Triphenyltin (TPT) compounds among PTs ranged from <0.1–25 ng g−1 ww and <0.1–61 ng g−1 ww in aquatic organisms from Merambong and Tinggi Island, respectively. A survey of OT concentrations among the species of OT compounds revealed that the concentrations of BTs and PTs in crabs and clams were high while those in fish were low. Correlation analysis with stable nitrogen isotopes suggest that OT compounds did not accumulate in aquatic organisms through the food web. The measurement of OT compounds in tissues and organs of fish revealed that BT concentrations in liver were higher than those in muscle and that BTs were detected in eggs of fish.